Pengembangan Lembar Kerja Mahasiswa Berbasis Pemberdayaan Berpikir melalui Pertanyaan pada Mata Kuliah Pengetahuan Lingkungan - Utami, Septiana Dwi; Dewi, Ika Nurani (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to develop a student worksheet based on the empowerment of thinking through questions in environmental knowledge courses. This type of research is development research using the R & D (Research and Development) method. In this study, only two stages of the R&D method were used, namely: 1) the preliminary study stage; and 2) the product development stage. The research was conducted in the Environmental Knowledge course. The instrument used to collect data was the Student Worksheet validation sheet which consisted of three components, namely: content, language, and presentation. Based on the results of the validation, the content component validation score obtained was 3.25 with valid criteria, the language component was 3.00 with valid criteria, and the presentation component obtained a score of 3.36 with valid criteria. Thus it can be concluded that, empowerment-based Student Worksheets think through questions on environmental knowledge courses with valid criteria and can be used as learning materials.